The Political Culture; Politicial Socialization and Acculturation - IOVAN, Marțian (Journal of Legal Studies, 2015)
In this article, the author, after having comparatively analyzed senses and significations of the concept of politic culture, as stated by several renowned authors in the world of science, proceeds to a differentiation of general political culture from those political cultures that are integrated into the lives of contemporary political agents (subcultures, political countercultures, marginal cultures, political cultures of public policy makers etc.) which coexist on the territory of a state. Using praxeological and systemic approaches, the author discusses the place and role of contemporary ideologies in their quality as a directional and dynamogenic factor in political practices, as well as political socialization and acculturation as methods of reproducing and developing political culture in accordance with the necessities imposed by the global development of society and by its subsystems. The formation of a solid political culture, through education and communication in general, both at individual and at social level, conditions the maturation of democracy, and the launching of public policies likely to solve individual and community issues.